Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Opportunities and challenges for use of minipigs in nonclinical pharmaceutical development: Results of a follow-up IQ DruSafe survey - David O. Clarke; Kaushik Datta; Kevin French; Michael W. Leach; Drew Olaharski; Susanne Mohr; Devon Strein; Jeanine Bussiere; Bianca Feyen; Beatrice E. Gauthier; Michael Graziano; Joanna Harding; et al. (Regulatory Toxicology and Pharmacology, 2024)

Using a GFP-labeled Stagonospora nodorum strain as a DNA extraction efficiency standard in plant disease diagnosis - Heting Fu; Yalong Yang; Kher Zahr; Shiming Xue; Junye Jiang; Michael W. Harding; David Feindel; Jie Feng (Crop Protection, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Plenodomus tracheiphilus, but not Dothiorella ulmi, causes wilt disease on elm trees in Alberta, Canada - Yalong Yang; Heting Fu; Kher Zahr; Shiming Xue; James Calpas; Krista Demilliano; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Discovery of three cycloviruses in fecal samples from silver-haired bats (Lasionycteris noctivagans) in Arizona (USA) - Ciara Harding; Brendan B. Larsen; Sophie Gryseels; Hans W. Otto; Crystal Suazo; Simona Kraberger; Nathan S. Upham; Michael Worobey; Koenraad Van Doorslaer; Arvind Varsani (Archives of Virology, 2022)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Plasmodiophora brassicae infection threshold—how many resting spores are required for generating clubroot galls on canola (Brassica napus) - Kher Zahr; Yalong Yang; Alian Sarkes; Snezana Dijanovic; Heting Fu; Michael W. Harding; David Feindel; Jie Feng (Journal of Plant Diseases and Protection, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

First report of Triticum mosaic virus infecting wheat in Canada - Harvinder Bennypaul; Ismail Abdullahi; Reem Aboukhaddour; Michael W. Harding (Journal of Plant Pathology, 2021)

Impact of DNA extraction efficiency on the sensitivity of PCR-based plant disease diagnosis and pathogen quantification - Yalong Yang; Qixing Zhou; Kher Zahr; Michael W. Harding; David Feindel; Jie Feng (European Journal of Plant Pathology, 2021)

Diversity in the population of Fusarium graminearum isolated from wheat and corn in Alberta, Canada - Hafiz Ahmed; Qixing Zhou; Kher Zahr; Yalong Yang; Heting Fu; Alian Sarkes; Yingli Wang; Krista Zuzak; David Feindel; Greg C. Daniels; Michael W. Harding; Jie Feng (Journal of Plant Diseases and Protection, 2020)

Assessing the availability of life cycle assessments in Austria - A. O. Ladenika; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

Review: the availability of life-cycle studies in Sweden - Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2019)

The availability of life-cycle assessment, water footprinting, and carbon footprinting studies in Brazil - Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; Taahira Goga; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

A discussion on the availability of life-cycle assessment studies in New Zealand - Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael O. Bodunrin; Nicholas W. Burman; Joel Croft; Taahira Goga; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Review: life-cycle assessment, water footprinting, and carbon footprinting in Portugal - Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Mpho Maepa; Michael Oluwatosin Bodunrin; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2018)

Review: life cycle assessments in Nigeria, Ghana, and Ivory Coast - Mpho Maepa; Michael Oluwatosin Bodunrin; Nicholas W. Burman; Joel Croft; Shaun Engelbrecht; A. O. Ladenika; O. S. MacGregor; Kevin G. Harding (The International Journal of Life Cycle Assessment, 2017)

Designing a sustainable monitoring framework for assessing impacts of climate change at Joshua Tree National Park, USA - Cameron W. Barrows; Josh Hoines; Kathleen D. Fleming; Michael S. Vamstad; Michelle Murphy-Mariscal; Kristen Lalumiere; Mitzi Harding (Biodiversity and Conservation, 2014)

Region‐wide changes in marine ecosystem dynamics: state‐space models to distinguish trends from step changes - Matthew Spencer; Nova Mieszkowska; Leonie A. Robinson; Stephen D. Simpson; Michael T. Burrows; Silvana N. R. Birchenough; Eva Capasso; Polly Cleall‐Harding; Julia Crummy; Callan Duck; Damien Eloire; Matthew Frost; et al. (Global Change Biology, 2012)
Regime shifts are sudden changes in ecosystem structure that can be detected across several ecosystem components. The concept that regime shifts are common in marine ecosystems has gained popularity in recent years. Many studies have searched for the step‐like changes in ecosystem state expected under a simple interpretation of this idea. However, other kinds of change, such as pervasive trends, have often been ignored. We assembled over 300 ecological time series from seven UK marine regions, covering two to three decades. We developed state‐space models for the first principal component of the time series in each region, a common measure of ecosystem state. Our models allowed both trends and step changes, possibly in combination. We found trends in three of seven regions and step changes in two of seven regions. Gradual and sudden changes are therefore important trajectories to consider in marine ecosystems.

Estuarine Ecosystem Response Captured Using a Synoptic Climatology - David G. Kimmel; W. David Miller; Lawrence W. Harding; Edward D. Houde; Michael R. Roman (Estuaries and Coasts, 2009)

Phytoplankton production, biomass and community structure following a summer nutrient pulse in Chesapeake Bay - Christina L.J. Yeager; Lawrence W. Harding; Michael E. Mallonee (Aquatic Ecology, 2005)

Correction - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. Heuvel; et al. (Phytoparasitica, 1998)

Abstracts of presentations on plant protection issues at the xth international congress of virology - Sijun Liu; Ian D. Bedford; Peter G. Markham; Morad Ghanim; Muhamad Zeidan; Henryk Czosnek; A. Bruyère; E. Herrbach; V. Brault; V. Ziegler-Graff; H. Guilley; J. F. J. M. van den Heuvel; et al. (Phytoparasitica, 1998)